2022
DOI: 10.1002/cncr.33805
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and opportunities to measuring oncology patient navigation impact: Results from the National Navigation Roundtable survey

Abstract: Background Patient navigation improves cancer care delivery for those most at risk for poor outcomes. Lack of sustainable funding threatens the full integration of navigation services into health care delivery systems. Standardized navigation metrics that document impact and identify best practices are necessary to support sustainability. Methods The National Navigation Roundtable administered a web‐based, cross‐sectional survey to oncology patient navigation programs to identify barriers and facilitators to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Evaluating the effect of patient navigator services in cancer care is an important requirement within a value‐based care system. Battaglia and colleagues 150 surveyed 538 patient navigation programs across the continuum of care in the United States, highlighting that only one half of these programs used data for reporting purposes. Of the 538 programs, 374 used electronic medical records, and only 25% of those 374 had an identifier for navigated patients using their service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the effect of patient navigator services in cancer care is an important requirement within a value‐based care system. Battaglia and colleagues 150 surveyed 538 patient navigation programs across the continuum of care in the United States, highlighting that only one half of these programs used data for reporting purposes. Of the 538 programs, 374 used electronic medical records, and only 25% of those 374 had an identifier for navigated patients using their service.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of time (55%) and lack of support (50%) for complex data system/platforms were the most common barriers to outcome data collection/reporting. In the survey used by Battaglia and colleagues, 150 there were useful metrics for consideration in future data‐collection and reporting activities. These metrics covered screening (eight items), cancer treatment (five items), survivorship (five items), and end‐of‐life care (five items).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bearing in mind the great variation in the definition of patient navigation, we recommend a standardized reporting of its components that would allow comparison between studies, external validity, replication in different settings and ultimately a better measure of its impact on cancer screening participation. The better reporting of navigation programmes together with a consistent data collection would facilitate sustainability 67 …”
Section: Discussionmentioning
confidence: 99%
“…The better reporting of navigation programmes together with a consistent data collection would facilitate sustainability. 67 A positive finding was that over 84% of studies reported 9 or more components out of 14, being supervision and addressing of social and emotional barriers the least reported. As in a previous review, 68 the duration of training on patient navigation was quite diverse.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was also disseminated through national, state, and local listservs, such as the membership of the Association of Oncology Nurse and Patient Navigators (AONN+) membership, the Oncology Nursing Society, the National Breast and Cervical Cancer Early Detection Program, and the Association of State Chronic Disease Directors. This recruitment method mirrored the method used in a previous NNRT cancer navigator national survey conducted in 2019 24 …”
Section: Methodsmentioning
confidence: 99%